The Effect of Gerlach & Ely Instructional Design Model and Learning Motivation on Elementary Students' Mathematics Achievement - Feni Peri Meswari; Darmansyah; Zelhendri Zen; Fetri Yeni (Jurnal Penelitian Pendidikan IPA, 2025)
This study investigates the low mathematics achievement observed in elementary students taught using conventional instructional approaches. The research aims to examine the effect of the Gerlach & Ely instructional design model and students’ learning motivation on mathematics achievement. A quasi-experimental method with a two-group design was applied, involving an experimental group receiving learning through the Gerlach & Ely model and a control group taught conventionally. Data were collected using a learning motivation questionnaire and a mathematics achievement test. Quantitative analysis, including comparison of mean scores and significance testing, was conducted to determine the effect of the instructional model and motivation levels. The findings show that students taught with the Gerlach & Ely model achieved significantly higher mathematics scores than those in the control group. High learning motivation also contributed positively to achievement, with motivated students outperforming those with lower motivation levels. Interaction analysis indicated that the Gerlach & Ely model remained effective across different motivation categories. The study concludes that structured instructional design has a substantial impact on improving mathematics performance and strengthening learning motivation. These results highlight the potential of adopting the Gerlach & Ely model more widely to enhance instructional quality in elementary mathematics education.